Weighted Temporal Utility - Anke Gerber; Kirsten I.M. Rohde (Tinbergen Institute, 2013)
We propose a novel utility representation for preferences over risky timed outcomes. The weighted temporal utility model generalizes many well known utility functions for intertemporal decision making under risk. A decision maker with a weighted temporal utility function can have time consistent yet non-stationary preferences or stationary yet time inconsistent preferences. Thus, our model can explain the empirical evidence in Halevy (2012) which is at odds with standard models of intertemporal choice that assume non-linear time perception to be the sole driver of non-stationary and time-inconsistent behavior. We also propose a non-parametric approach to elicit a weighted temporal utility function.
Keywords: D91; D81; 330; Intertemporal choice; stationarity; time consistency